Strategic Investment in the Research and Development of Memristor Technology in the Republic of Serbia - Bojić, Ljubiša; Чабаркапа, Милан (Napredak, 2024)
The rapid advancement of Artificial Intelligence (AI) has significantly impacted both high technology development and economic and social progress. The Republic of Serbia has been strategically supporting research and development of in the field of AI. Given the dramatic dynamic development of AI, the aim of this paper is to identify and describe memristor technology as currently very relevant and attractive, in order to achieve technological innovation, socio-economic benefits, and potentially global breakthroughs. The paper presents an overview of literature to analyze theoretical concepts, current research outcomes in AI, and possible applications of memristors. The analyses indicate that adoption and development of memristor technology in Serbia can position the country as a leader in AI hardware innovation, attracting international partners and fostering a technologically advanced industrial system. Therefore, this paper suggests that future research should focus on overcoming practical challenges in the production of memristors, developing hybrid architectures, and formulating advanced neuromorphic algorithms.
Keywords: memristors; neuromorphic computing; technological innovation; strategic positioning; global breakthrough